The Nexus Between Inflation and Money Supply in Sri Lanka: An ARDL Bounds Test - Francis, S.J.; Danthanarayana, C.T.; Basnayake, B.M.A. (MENTOR The Journal of Business Studies, 2024)
Monetary tools, money supply, and exchange rates play a significant role in a country's growth and significantly impact its development trajectory. Sri Lanka is currently concerned about high inflation. Inflation is a monetary phenomenon, and it has been caused by monetary policies in several nations. The relationship between money supply and inflation has been a topic of enduring interest and debate in economics. This paper aims to investigate the examine the causal relationship between money supply and inflation. This empirical study analyses short run and long run relationship between inflation and money supply, during 1978-2023 in Sri Lanka. Annual data for the period 1978-2023, obtained from annual reports of Central Bank of Sri Lanka were used for this study. This study employs Autoregressive Distributed Lag (ARDL) Bounds test to identify the long run and short run relationship between inflation and its causes. The findings of the study indicate that nominal exchange rate has both short run a nd long run relationships with inflation while nominal money supply and nominal interest rate have a long run relationship with inflation but not a short run relationship. According to results of the study, money supply and inflation have a positive relationship in the long run. Thus, classical quantity theory of money and Cambridge equation as well as monetarist view on inflation is valid in the long run in Sri Lanka. When considering the nexus between inflation and interest rate, it is concluded to have a positive relationship in Sri Lankan context. A positive relationship can be seen in between nominal exchange rate and inflation in both short term and long term. Therefore, in order to achieve price stability, proper control over monetary policy and proper management of e xchange rates are important.
Keywords: ARDL model; Error correction model; Inflation; Money Supply